IMPROVING PATIENT SAFETY IN HEALTHCARE: A COMPREHENSIVE APPROACH FROM PHARMACY, LABORATORY, RADIOLOGY AND NURSING TEAMS - Fatema Abdulmohsen Alnasser, Fatimah Ali Al Omran, Zahra Hilal Al Sayegh, Ebtisam Amir Alnahdi, Fadwa Saeed Alalawi, Saleh Ali Rashed Alabbas,Fares Hamad Hussain Alyami (Chelonian Research Foundation, 2022)
Introduction: The Institute ofMedicine objectives for the healthcare sector in terms of safety, effectiveness, patient-centeredness, efficiency, timeliness, and equality have not yet been met. The skills needed to provide high-quality healthcare are not adequately taught in current professional curricula, especially for pharmacy, laboratory, nursing and radiology professionals who will soon be entering thefield. Aim of work: To provide a comprehensive assessment of the roles pharmacy, laboratory, radiology and nursing teams in improving patient safety in Healthcare. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: pharmacy, laboratory, radiology, nursing teams, improving, patient, safety, Healthcare. The search was restricted to publications from 2016 to 2021 in order to locate relevant content. I performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: The role of pharmacists in patienlt safety is expected to grow as prescription errors remain a significant concern. They can play a crucial role in reducing adverse occurrences and enhancing healthcare safety. Clinicians play a vital role in reducing errors before laboratory analysis. Training programs can enhance specimen collection quality. Incorporating laboratory experts in clinical rounds, patient safety committees, and training seminars can facilitate information sharing. A comprehensive plan of action is essential to increase awareness of radiation hazards andfacilitate the dissemination of education. Nurses play a crucial role in patient safety, influenced by their work environment and supervisor support. Nurse leaders can cultivate a culture ofpatient safety and improve clinical outcomes by effectively managing these issues. Keywords: Pharmacy, Laboratory, Radiology, Nursing Teams, Improving, Patient, Safety, Healthcare.